Studi Aplikasi Sistem Energi Surya Fotovoltaik Hibrid Tanpa Sinkronisasi di Ponpes Mahfilud Duror - Andi Setiawan (Fakultas Teknik, Universitas Jember, 2015)
AbstractA study of the photovoltaic (PV) system implementation in aneducational institution has been done and leads to the conclusionthat economically there is no reason that could make this into afeasible implementation plan. However, this technology has beenvery mature and needs to be implemented as an activity that has avisionary goal. In this deployment scenario, SESF is hybridconfigured with PLN without synchronization. To make this systemproduces a more optimum benefits, some engineering activities isrequired such as reconfiguration of system load and loadscheduling to reduce the wasted excess energy during the day.Keywords—PV system, renewable energy, hybrid system